Gly Betaine Surpasses Melatonin to Improve Salt Tolerance in Dalbergia odorifera - Cisse, El Hadji Malick; Miao, Ling-Feng; Yang, Fan; Huang, Jin-Fu; Li, Da-Dong; Zhang, Juan (Frontiers in Plant Science, 2021)
Salinity is one of the most serious factors limiting plant growth which can provoke significant losses in agricultural crop production, particularly in arid and semi-arid areas. This study aimed to investigate whether melatonin (MT; 0.05 and 0.1 mM), which has pleiotropic roles, has a better effect than glycine betaine (GB; 10 and 50 mM) on providing salt tolerance in a woody plant Dalbergia odorifera T. Chen. Also, the alternative oxidase activity (AOX) in plant subjected to MT or GB under salinity (150 and 250 mM) was evaluated given that the effect of exogenous MT or GB on AOX has not been reported yet. The results showed that the exogenous application of GB on the seedlings of D. odorifera increased the plant growth parameters, relative water content, total of chlorophyll content, and carotenoid content compared with well-watered and MT treatments. Under severe salinity, the seedlings subjected to GB showed, a significant enhancement in water use efficiency, transpiration, and net photosynthetic rate regardless to MT-treated seedlings. The levels of proline and soluble sugar in the seedlings treated with MT or GB decreased significantly under mild and severe salinity correlated with those in salt-stressed seedlings. Furthermore, GB-treated plants exhibited a significant inhibition of malondialdehyde content compared with MT-treated plants. The concentration of thiols and phenolic compounds were significantly enhanced in the leaves of seedlings treated with MT compared with those treated with GB. Under salt stress condition, GB scavenged significantly higher levels of hydrogen peroxide than MT; while under severe salinity, plants subjected to MT showed better scavenging ability for hydroxyl radicals compared with GB-treated seedlings. The results demonstrated also an enhancement of the levels of superoxide dismutase, guaiacol peroxidase, and AOX activities in seedlings treated with GB or MT compared with salt-stressed plants. The catalase activity was increased by 0.05 mM MT and 0.1 mM GB under mild salinity. Meanwhile, the AOX activity under severe salinity was enhanced only by GB 50 mM. The findings of this study suggested that GB- treated seedlings possessed a better salt tolerance in comparison with MT-treated seedlings.